P-015 High Resolution- MRI Features of Reversible Cerebral Vasoconstriction Syndrome Over Time. (14th July 2013) - Cerejo, R; Hui, F; Jones, S; Obusez, E; Hammad, T; Hajj-ali, R; Uchino, K
Abstract : Introduction: Reversible Cerebral Vasoconstriction Syndrome (RCVS) is associated with thunderclap headache, subarachnoid haemorrhage and potential ischaemic sequelae, with very different management than traditional central nervous system vasculitides. The advent of vessel wall imaging may help differentiate RCVS from other lesions, however knowledge of the imaging features of the syndrome over time may help physicians make the diagnosis with greater confidence. Methods: The Cleveland Clinic 3-Tesla High resolution MRI (HRMR) database was retrospectively reviewed to identify patients with clinically diagnosed RCVS that also received HRMR yielding a total of 13 patients. Imaging protocol included black-blood gadolinium contrast-enhanced T1-weighted sequence with fat suppression and time-of-flight MRA of the circle of Willis. Imaging features were assessed by 2 experienced neuro-radiologists and indexed to time of imaging relative to the date of symptom onset. The images were then placed in sequential order, and features summarised as a function of time as an aggregate of patients. Findings: The median age was 52 years with 2/13 (15%) being males. Median time to scan from symptom onset was 0.5 months. Mild vessel wall enhancement and thickening was noted in 4 patients (30%), while 6 patients had wall thickening alone. Remaining 3 patients only showed multifocal stenosis. Three patients (23%) were on steroids at time of initial scan. Nine patients (63%) had follow up imaging with a median follow up of 2.5 months. At follow up, 7/9 patients showed resolution of the enhancement and wall thickening while 1 patient had mild vessel wall enhancement and another had vessel wall thickening. Conclusion: In this limited retrospective review of RCVS patients, there is a clear improvement over time in terms of vessel wall enhancement and thickening. Vessel wall thickening and enhancement was more vivid at earlier time points and reduced over time. HRMR imaging of the vessel walls may provide corroboration of clinical onset and track resolution of RCVS as well as differentiate the disease from other vasculopathies. Further research is needed. Disclosures: R. Cerejo: None. F. Hui: None. S. Jones: None. E. Obusez: None. T. Hammad: None. R. Hajj-ali: None. K. Uchino: None.